Investigasi Desain Pengajaran untuk Penalaran Matematis - Novita Fatmiyati; Freddy Prasetyo; Dela Ambarwati; Dadan Dasari (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2023)
Abstract:Learning mathematics requires students to have various abilities and skills, including mathematical reasoning ability. This study aims to identify any matters related to teaching design in mathematics education toward students' mathematical reasoning abilities. The method used was Systematic Literature Review (SLR) and the collection of literature used as research subjects were carried out by searching the Scopus database and using inclusion criteria in the form of (1) written in English, (2) published in the last ten years (2013-2022), and (3) indexed by Scopus. There are 24 articles identified that meet the inclusion criteria and were analyzed based on teaching design categorization by van der Akker that has been modified by Lithner. The results found that there are learning designs that affect various mathematical reasoning abilities, namely the Zone of Proximal Development (ZPD), Realistic Mathematics Education (RME), and Theory of Didactical Situation (TDS), where various claims in the form of interventions such as learning models, learning instructions and teaching media or materials, which have been seen to effectively improve students' mathematical reasoning abilities. Abstrak:Pembelajaran matematika menuntut kemampuan dan keterampilan siswa, salah satunya kemampuan penalaran matematika. Penelitian ini bertujuan mengindentifikasi desain pembelajaran matematika terkait kemampuan penalaran matematis siswa. Metode yang digunakan yaitu Systematic Literature Review (SLR) dengan mengidentifikasi database Scopusdengan kriteria inklusi berupa (1) ditulis dalam Bahasa Inggris, (2) diterbitkan selama sepuluh tahun terakhir (2013-2022), dan (3) terindeks Scopus. Terdapat 24 artikel yang teridentifikasi memenuhi kriteria tersebut yang selanjutnya dianalisis berdasarkan kategorisasi desain pengajaran menurut van der Akker yang dimodifikasi oleh Lithner. Hasil penelitian ini menemukan terdapat desain pengajaran yang mempengaruhi berbagai kemampuan penalaran matematis, yaitu Zone of Proximal Development (ZPD), Realistic Mathematics Education (RME), dan Theory of Didactical Situation (TDS), dengan berbagai klaim diantaranya intervensi model pembelajaran, instruksi pembelajaran, dan media atau bahan ajar, yang secara efektif meningkatkan kemampuan penalaran matematika siswa.